História/s e historiografia/s de línguas: Apresentação - Procópio, Eliabe dos Santos; Marengo, Sandro Marcío Drumond Alves; Alexandre, Diego José Alves (Revista Diálogos | Estudos da Linguagem, 2022)
Organização: Prof. Dr. Eliabe dos Santos Procópio Prof. Dr. Sandro Marcío Drumond Alves Marengo Prof. Dr. Diego José Alves Alexandre